Estimation of the congestion cost of the Portuguese National Transmission Network - Evolution from 1998 to 2008 - João Tomé Saraiva (2012)
This paper describes the models that were used and the results obtained to estimate the Congestion Cost of the Portuguese National Transmission Network. This network is established at 400 / 220 and 150 kV and the Tariff Code in force is Portugal determines the use of a postage stamp based approach discriminated by voltage level to set the tariffs for the use of the transmission system. However, the value of the congestion cost and its percentage regarding the regulated revenue of the transmission activity set by the Regulatory Agency are good indicators of the quality of the network since they directly reflect problems in the network in terms of congested branches or larger transmission losses. In this sense, we have been computing this indicator since 1998 and this paper reports the conclusions that were recently obtained using data from 2006 and 2008.